Relaxant Effects of Essential Oils Of Eucalyptus Camaldulensis on Aortic Rings in Male Albino Rats - Al-Habib, Omar A. M.; Kheder, Dlzar A.; Gilardoni, Gianluca (Science Journal of University of Zakho, 2013)
The essential oil (EO) produced a potent dilation in aortic rings with percentage of relaxation 95.659%.The significant relaxant effect on thoracic aortic rings was inhibited by GLIB (10-5) and 4-AP (1mM)with percentages of relaxation, 74.577% and 51.494%, respectively. On the other hand, vasorelaxation in aortic rings did not influenced by pretreatment with TEA and BaCl2. Pretreatment of aortic rings with nifedipine, significantly blocked the relaxation to 38.7%. On the other hand, the dose-response shifted to the right in endothelium denuded preparation. The percentage of relaxation in endothelium-denuded was 82.28%. Preincubation of aortic rings with L-NAME and Indomethacin altered the dilation from control significantly, and the percentage of relaxation found to be 60.18% and 77.077%, respectively. The present study suggest that the EO of E .camaldulensis depresses the aortic force development, probably acting as a Ca++ channel antagonism and partially via NO and cyclooxygenase pathways, the involvement of KATP and KV channels in the vasorelaxatoin induced by EO.